12 Barriers and facilitators to using real-world data in healthcare settings in low-and middle-income countries: a systematic review of qualitative studies. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Soliman, Ranin; Roberts, Nia; Elhaddad, Alaa; Eweida, Wael; Oke, Jason; Heneghan, Carl
Abstract : Objectives: To determine the barriers and facilitators to using real world data (RWD) in healthcare settings in low-and middle-income countries (LMICs). Method: We conducted a systematic review through searching MEDLINE, EMBASE, Global Health Database and CINAHL. We searched for qualitative studies that address the use of RWD, barriers and facilitators, and its applications in LMICs. Study participants included healthcare settings/organizations in LMICs which collect and use RWD. Primary outcomes are the roles of using RWD, and barriers/facilitators affecting the applications of RWD in healthcare settings in LMICs. Data extraction included contextual and methodological data. Quality of review will be assessed using the CASP Qualitative checklist, and we will follow the ENTREQ checklist for synthesis of qualitative research. Risk of bias will be assessed using GRADE-CERQual to determine the level of confidence from qualitative evidence synthesis. Qualitative data synthesis will be done as narrative/descriptive synthesis of the roles of using RWD in healthcare settings in LMICs; thematic synthesis and conceptual framework of the barriers/facilitators of using RWD and its applications. Results: The review addressed the use of real-world data in healthcare settings in LMICs, according to World Bank classification including 137 countries as per World Bank country classification. Initial search across the four databases showed a total of 2, 245 search results. The results were separated into three sets; systematic reviews (n = 27) from 2012 until 2018; primary studies (n = 2, 048) from 1988 until 2019; and conference abstracts (n = 170) from 2004 until 2018. Preliminary searches are completed, and piloting of the study selection process was done. Formal screening of results against eligibility criteria is underway and will be presented in conference. Conclusions: The use of RWD in healthcare settings in LMICs is important to make evidence-based improvements in care delivery and health outcomes. Results from this systematic review will address the gap in evidence about what real world data is used in LMICs and the barriers and facilitators to its use. This review will generate qualitative evidence about the roles, barriers and facilitators and real-world applications of using RWD in healthcare settings in LMICs.